The Equation of State of Biogas - Petr Trávníček (Acta Universitatis Agriculturae et Silviculturae Mendelianae Brunensis, 2017)
The presented work deals with a state behavior of real gas, biogas. Theoretical approach was utilized for processing of this work. Compressibility factor was calculated with help of two equation of state – Van der Waals equation and Redlich‑Kwong equation. Constants a and b of both equations were calculated using geometric average of the constants of pure substances. On the basis of calculated data charts showing the dependence of compressibility factor and the pressure were created. These charts were created for temperatures 20 °C and 40 °C. Statistical analyses of data were carried out. The results showed that compressibility factor reached value from 0.997 to 0.97 (20 °C) and from 0.997 to 0.974 (40 °C) in the case Van der Waals equation and in the range of pressure from 100 kPa to 1000 kPa. In the case of Redlich‑Kwong equation these values were from 0.997 to 0.967 (20 °C) and from 0.997 to 0.974 (40 °C) in the same range of pressures.